Analisis Fenomena Defisit Anggaran dan Defisit Transaksi Berjalan di Indonesia (1990-2019) - Mayang Novi Annisa Perdana; FX Sugiyanto (Universitas Diponegoro, 2021)
This research is motivated by the occurrence of twin deficit in Indonesia that have occurred since 2012. Twin deficit is a phenomenon where the budget deficit occurs simultaneously with the current account deficit. The relationship between the government budget and the current account is explained through components in the APBN and the current account balance. Therefore, this study aims to analyze the correlation between the budget deficit and the current account deficit. This study uses time series data for the period 1990-2019, obtained from Kementrian Keuangan Republik Indonesia, Bank Indonesia and World Bank publications. The method used in this study is the Vector Error Correction Model (VECM) regression method to see the short-term and long-term relationships of budget deficit to the current account deficit. The results of this study indicate that there is a correlation between the budget deficit and the current account deficit. This is indicated by the empirical results which show that significantly the budget deficit has a correlation with the current account deficit in the short and long term. In the period 1990-1999, the budget balance and the current account showed no correlation. The current account deficit in that period was mainly due to investment patterns. The existence of a balance relationship between the budget balance and the current account is shown in the 2000-2019 period, during which Indonesia implemented a deficit budget system.